Method of axial adjustment for precessional transmissions - Bostan Ion; Mazuru Sergiu; Casian Maxim (MATEC Web of Conferences, 2018)
Axial adjustment method for precessional transmissions includes compensation error calculation, determination compensator groups, achieved in the form of base and auxiliary rings. The compensator has on the base ring axial canals in which can be placed clamping bolts but the auxiliary ring has axial holes for the screws. The auxiliary ring is formed from increasing sectors - the distance between auxiliary ring stairs and front side of body, from decreasing sectors - the distance between base ring and bottom place, and the closure element - the clearance between gear body and the front surface of the base ring. According to the method of group interchangeability is determined the deviation value of the upper and lower group tolerance and the clearance between lid and body. Then rotating one of the rings is ensured the dimension of the compensator which must match to compensation clearance value and then the compensator is adjusted to required value.